ANALYSIS OF COMPETENCY NEEDS FOR LATHE MACHINE OPERATORS IN THE MEDIUM-SCALE MANUFACTURING INDUSTRY IN THE CITY OF SERANG - dika, Ardhika Achmad Gustama; Ananda Yhuto Wibisono Putra (Politeknik Negeri Cilacap, 2024)
Lathe operator competence is needed in every manufacturing industry, especially in the field of turning. Currently, employment in Indonesia, especially in the manufacturing industry, has increased from year to year, so it is necessary to identify the work and tasks of a lathe operator. This study aims to (1) identify the work and (2) tasks of lathe operators in the medium scale manufacturing industry. The method used in this research is the descriptive qualitative method. The object of this research is a lathe operator from a medium sized manufacturing industry in Serang city, Indonesia. For data collection, this study used observational studies. The data analisys technique used was descriptive analysis and Dacum Research Chart which was validated by Expert Judgement. This study successfully identified (1) Five types of work and (2) Twenty-two tasks performed by a lathe operator in a medium-scale manufacturing industry with sixteen knowledge and skills as well as eight attitudes that must be possessed by a lathe operator and as many as forty-one machines and supporting tools whose operation must be controlled by a lathe operator in a medium-scale manufacturing industry.